Predictors and variability of drug‐eluting vs bare‐metal stent selection in contemporary percutaneous coronary intervention: Insights from the PRISM study. Issue 8 (16th March 2017) - Shafiq, Ali; Gosch, Kensey; Amin, Amit P.; Ting, Henry H.; Spertus, John A.; Salisbury, Adam C.
Abstract : Drug‐eluting stents (DES) reduce risk of in‐stent restenosis after percutaneous coronary intervention (PCI) but require dual antiplatelet therapy (DAPT) for a longer term than bare‐metal stents (BMS). Few studies have examined clinical predictors of DES vs BMS, and variability in provider selection between DES and BMS in clinical practice has not been well described. These insights can inform our understanding of current practice and may identify opportunities to improve decision‐making stent selection decinsion‐making. In a multicenter registry, 3295 consecutive patients underwent PCI by 158 interventional cardiologists across 10 US sites. Eighty percent of patients with treated with DES. Using hierarchical regression, diabetes mellitus, multivessel disease, health insurance, and white race were independently associated with greater DES use, whereas increasing age, history of hypertension, anticipated surgery, use of warfarin, lower hemoglobin, prior history of bleeding, and treatment of right coronary and left circumflex artery lesions as compared with PCI of left anterior descending artery were associated with lower likelihood of receiving DES. Adjusted rates of DES use across providers varied from 52.3% to 94.6%, and adjusted median odds ratio for DES selection was 1.69. DES selection appeared to reflect physicians' attempts to balance benefits of DES against risks of prolonged DAPT. Nevertheless, marked residual variability in DES selection across providers persisted after adjusting for predictors of restenosis, bleeding, and other factors. Further studies are needed to better understand drivers of this variability and identify the impact of patient and provider preferences on stent selection at the time of PCI.